(untitled) (Biological Sciences - PJSIR, 2025)
Present studies were conducted on some trees and herbs of the Cholistan desert, Pakistan based on solvent dependent extraction of non-enzymatic antioxidants i.e. alkaloids, flavonoids and saponins. Three different extraction solvents i.e. ethanol, methanol and acetone were used. The results revealed that ethanol has maximum extraction potential followed by methanol and then acetone. In trees, alkaloid contents were in order Acacia jacquemontii >Tamarix aphylla >Acacia nilotica >Capparis decidua>Prosopis cinerari. Among herbs, Citrullus colocynthis gave more alkaloids than Tribulus longipetalus. Flavonoids ratios were as methanol >ethanol >acetone. Flavonoids in trees were as Acacia jacquemontii>Capparis decidua >Prosopis cineraria >Tamarix aphylla >Acacia nilotica. Among herbs, Flavonoids were obtained maximally from Solanum surattense and the lowest in Launaea nudicauli. For saponin, methanol was found to be the most powerful extraction solvent. The maximum concentrations of saponins were found in Acacia jacquemontii and Tribulus longipetalus of trees and herbs respectively. These findings provide valuable insights into solvent dependent extraction methods for non-enzymatic antioxidants present in the Cholistan desert flora, offering potential avenues for further exploration in pharmaceutical and nutritional applications.